An Analysis of EFL College Students’ Anxieties in Listening and Reading Skills at English Department FBS UNP - Hidayatul Fadhilah; Leni Marlina (Journal of English Language Teaching, 2022)
This study aims to compare the level of foreign language anxiety in listening and reading skills of EFL students in English language education study program and English language literature study program at  FBS UNP. This research employed the following questionnaires as the research instruments: Foreign Language Listening Anxiety Questionnaire (FLLAQ) adapted from Marzec-Stawiarska (2013) and Foreign Language Reading Anxiety Questionnaire adopted from Azhari Muhlis (2017). The results of this study indicated that the majority of the English language education program students and English language literature program students of UNP have a high level of foreign language anxiety in listening and reading skills. To accomplish a better learning outcome, it is strongly advised that students become aware of their anxiety and deal with it through a lot of practice, peer-to-peer support, and optimistic thought. Furthermore, teachers can be more innovative in making language skills classes more enjoyable and relaxing for students to accomplish better learning outcomes.